LEGO-Lipophosphonoxin membrane activity is enhanced by presence of phosphatidylethanolamine but hindered by outer membrane - Hana Brzobohatá; Milica Dugić; Viktor Mojr; Nitjawan Sahatsapan; Ivana Kóšiová; Tomáš Křížek; Tereza Dolejšová; Petra Lišková; Lukasz Cwiklik; Dominik Rejman; Radovan Fišer; Gabriela Mikušová (Scientific Reports)
Abstract Finding effective antibiotics against multi-resistant strains of bacteria has been a challenging race. Linker-Evolved-Group-Optimized-Lipophosphonoxins (LEGO-LPPOs) are small modular synthetic antibacterial compounds targeting the cytoplasmic membrane. Here we focused on understanding the reasons for the variable efficacy of selected LEGO-LPPOs (LEGO-1, LEGO-2, LEGO-3, and LEGO-4) differing in hydrophobic and linker module structure and length. LEGO-1–4 permeabilized cytoplasmic membrane of Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, and Escherichia coli, LEGO-1 with the longest linker module being the most effective. Gram-positive bacteria were more sensitive to LEGO-LPPO action compared to Gram-negatives, which was manifested as a delayed membrane permeabilization, higher minimal inhibitory concentration and lower amount of LEGO-LPPO bound to the cells. Outer membrane permeability measurements and time-kill assay showed that presence of the intact outer membrane brought about reduced susceptibility of Gram-negatives. Using liposome leakage and in silico simulations, we showed that membranes with major content of phosphatidylethanolamine were more prone to LEGO-LPPO permeabilization. The proposed mechanism stems from an electrostatic repulsion between highly positively charged LEGO-1 molecules and positively charged amino groups of phosphatidylethanolamine which destabilizes the membrane. Collectively, these data suggest that LEGO-LPPO membrane activity is enhanced by presence of phosphatidylethanolamine but hindered by presence of intact outer membrane.